MINERAL COMPOSITION of RAW MATERIAL, SUBSTRATE and FRUITING BODIES of Pleurotus ostreatus IN CULTURE - Sales-Campos, Ceci; da Eira, Augusto Ferreira [UNESP]; de Almeida Minhoni, Marli Teixeira [UNESP]; Nogueira de Andrade, Meire Cristina (Interciencia, 2009)
In a culture of a Pleurotus ostreatus (oyster mushroom) strain, macro and micronutrients of the raw material and the initial and spent substrates were evaluated. Substrates were formulated with sawdust from Simarouba amara Aubl. and Ochroma piramidale Cav. ex. Lam., crushed Bactris gasipaes Kunth and crushed Saccharum officinarum (sugar cane). Samples were solubilized by means of acid digestion (nitric-peridrol). Ca, Mg, Fe, Cu, Zn and Mn were determined by atomic absorption spectrophotometry, Na and K by atomic emission, and P by colorimetry. The mineral composition of the fruiting body varied with the substrates, which made possible the production of a fruiting body rich in K, P Mg and Fe. Potassium was the mineral with the highest content in the fruiting body in all substrates tested (36.83-42.18g.kg(-1)). There was an increase of protein and mineral content in the spent substrate in relation to the initial one.
Keywords: Mineral Composition; Mushrooms; Pleurotus ostreatus